AUTHOR’S DICTIONARIES AS AN OBJECT OF LINGUISTIC RESEARCH - Farangiz Makhmudova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, what is a dictionary of authorship, its place and features in linguistics, the emergence and development of lexicography of authorship in Uzbek linguistics, how works related to the lexicography of authorship in our classical literature were created, differences and general characteristics of written dictionaries. The article examines the importance of author’s lexicographical dictionaries in modern Uzbek linguistics.